Vocatives of Ferdinand E. Marcos in Philippine Newspaper Articles: Forms, Structures, Positions and Pragmatic Inferences - Richard Sambajon Agbayani (Randwick International of Education and Linguistics Science Journal, 2022)
This paper intends to provide details with regard to the forms, structures and positions of vocatives prevalently utilized by writers to address former President Ferdinand E. Marcos in news articles of the three leading Philippine newspapers (Philippine Daily Inquirer, The Philippine Star, and Manila Bulletin). A total of 90 news article samples were collected and pragmatically analyzed to answer the research questions at hand. Results revealed that Filipino news article writers favored the use of single- word and phrase forms of vocatives. As regards the vocatives structures, one – word noun (N) structure , Adj. + N + N, Det + Adj. + N, and Det + N phrasal structures are predominant in the top three dailies. Also, medial is the most preferred vocative position followed by initial then final position. Since vocatives have pragmatic implications, the employment of address forms (e.g. dictator, strongman, the author of Martial Law, and tyrant) to refer to Marcos suggests negativity as these terms indicate inappropriateness in the context of use. Consequently, it can be inferred that while writers’ presentation of Marcos in their articles exhibits fairness, there is a general lack of sensitivity and awareness regarding the suitable usage of some vocatives in Philippine culture.